Oceanography and coastal morphology of Ao Phai - Siripong Siriswatdibutr; Suphat Vongvisessomjai; Tawatchai Tingsanchali; Prida Thimakorn; USAID-ASEAN (Bangkok : Asian Institute of Technology, 1982)
The location and site topography of t he Ao Phai area provide a favourable and feasible condition to construct a large scale power plant. Therefore special attention must be paid to provide the necessary information for designing coastal structures. This study aims at analyzing tides, tidal current, wave and their induced littoral transport and suspension depth in the Ao Phai area. In Ao Phai, where a tidal current is predominant, fifteen days hourly data at 13 locations over the area are analyzed by harmonics analysis in order t o obtain the whole pattern of the current. Since tidal currents are dependent on tides a nd water depth, t heir functional relationship was established, so that the magnitude and direction of the tidal current ·at any location over Ao Phai could be predicted. The significant wave height and wave period are computed from the wind data, collected by EGAT, for a period of ten year s (1973-1982) , in order to obtain t he longshore transport and depth of suspension. As well, the probability of occurrence of t he significant wave height and wave period were well fitted to the normal distribution, as was the suspension depth t o the log normal distribution. As a result, the magnitude of both at any probability of occurrences could be obtained. It is found from the study that there exists a functional relationship between tide and tidal current; the influence of wave in suspending bed sediment is limited to a depth less than 5 meters (95% of the time). Finally, because t he annual littoral transport was moderate i.e. in the order of ten thousand cubic meters, it is the author' s 0pinionthat any designer should consider such effects.
A thesis submitted in partial fulfillment of the requirement for the degree of Master of Engineering, School of Engineering and Technology
Thesis (M.Eng.) - Asian Institute of Technology, 1982
Keywords: Oceanography -- Ao Phai